Reconceptualizing the Family to Improve Inclusion in Childhood Disability Research and Practice - Phoenix, Michelle; Reitzel, Meaghan; Martens, Rachel; Lebsack, Jeanine (Frontiers in Rehabilitation Sciences, 2021)
The World Health Organization’s International Classification of Functioning, Disability and Health recognizes that environmental factors impact well-being and life participation for children with disabilities. A primary environment in which children grow and learn is the family. The importance of family has long been recognized in family-centered practice and family-centered research. Although family-centered services and research have been critically explored, the concept of family has received less critical attention in rehabilitation literature. The family construct is due for an updated conceptualization with careful consideration of the implications for childhood disability rehabilitation practice and research. Interrogating the family construct asks questions such as: who is included as a part of the family? Which family structures are prioritized and valued? What is the potential harm when some families are ignored or underrepresented in childhood disability practice and research? What implications could a modern rethinking of the concept of family have on the future of childhood rehabilitation practice and research? This perspective article raises these critical questions from the authors’ perspectives as parents of children with disabilities, child focused rehabilitation professionals, and researchers that focus on service delivery in children’s rehabilitation and family engagement in research. A critical reflection is presented, focused on how the construct of family affects children’s rehabilitation practice and research, integrating concepts of equity, inclusion and human rights. Practical suggestions for children’s rehabilitation service providers and researchers are provided to aid in inclusive practices, critical reflection, and advocacy.